The use of an ontology as support of a virtual lab and remote labs network Euronet - Lab - Correia, Raúl Cordeiro (2014)
Our propose is to build a network of virtual laboratories, based in a Virtual Closet that will contain all the elements and parts that are needed to build the various experiences available in a v-labs network (that we call Euronet-Lab). To build this complex network we need to find a system that supports effectively this structure. This probably will be a enormous database of v-labs and independent elements, where will be possible sometimes to “recycle” some of the elements. This means “re-use” the same element several times in many experiences. To do this is necessary to have a structure that allows us to have several instances of the same element. It’s important that in our structure and virtual environment we can create several “images” of the same reality and this images can be used simultaneously in different circuits/experiments. This means that we can create several instances of the same element, to be used in different experiences and exercises.